Supporting asynchronous collaboration in visual analytics systems - Henry Riche, Nathalie; Inkpen, Kori; Stasko, John; Gross, Tom; Czerwinski, Mary (AVI '12 Proceedings of the International Working Conference on Advanced Visual Interfaces, 2012)
Visual analytics involves complex analytical processes that can often benefit from collaboration. Many researchers have explored co-located synchronous systems to help support collaborative visual analytics; however, the process can often be long and require a series of sessions. Providing support for asynchronous collaboration in visual analytics systems can help divide the problem between several analysts across many sessions to ensure that they can effectively work together toward a solution. Currently, visual analytics systems offer limited support for asynchronous, multi-session work [1]. In this workshop, we seek to bring together researchers from both the CSCW and Visual Analytics communities to discuss avenues for supporting asynchronous collaboration in visual analytics system.